Engineering Dissipation with Resistive Elements in Circuit Quantum Electrodynamics. Issue 11 (24th September 2021) - Cattaneo, Marco; Paraoanu, Gheorghe Sorin
Abstract: The importance of dissipation engineering ranges from universal quantum computation to non‐equilibrium quantum thermodynamics. In recent years, more and more theoretical and experimental studies have shown the relevance of this topic for circuit quantum electrodynamics, one of the major platforms in the race for a quantum computer. This article discusses how to simulate thermal baths by inserting resistive elements in networks of superconducting qubits. Apart from pedagogically reviewing the phenomenological and microscopic models of a resistor as thermal bath with Johnson–Nyquist noise, the paper introduces some new results in the weak coupling limit, showing that the most common examples of open quantum systems can be simulated through capacitively coupled superconducting qubits and resistors. The aim of the manuscript, written with a broad audience in mind, is to be both an instructive tutorial about how to derive and characterize the Hamiltonian of general dissipative superconducting circuits with capacitive coupling, and a review of the most relevant and topical theoretical and experimental works focused on resistive elements and dissipation engineering. Abstract : This article discusses how to simulate thermal baths by inserting resistive elements in networks of superconducting qubits. Its aim is to be both an instructive tutorial about how to derive and characterize the Hamiltonian of general dissipative superconducting circuits with capacitive coupling, and a review of the most relevant theoretical and experimental works focused on resistive elements and dissipation engineering.